2012
DOI: 10.4103/0972-2327.100018
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural management of migraine

Abstract: It is important to recognise that migraine is a ‘biological’ and not a ‘psychological’ entity. However, psychological factors can be involved in migraine in 4 different ways:- 1) Migraines can be triggered by psychological stressors; 2) Severe migraine can itself be a cause of significant psychological stress which can, in turn, exacerbate the problem; 3) Even if psychological stress is not significantly involved in the genesis of the headache, pain management techniques can help people cope with their pain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Concerning care for migraine patients, behavioral approach techniques are reported to be the most useful therapy to recognize and deal with feelings (Holroyd & Drew, 2006; Pizza et al, 2001; Weatherby, Brown, Newman, & Noad, 2012). However, our results highlight that migraine patients have a specific functioning that cannot be treated solely by a behavioral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning care for migraine patients, behavioral approach techniques are reported to be the most useful therapy to recognize and deal with feelings (Holroyd & Drew, 2006; Pizza et al, 2001; Weatherby, Brown, Newman, & Noad, 2012). However, our results highlight that migraine patients have a specific functioning that cannot be treated solely by a behavioral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of this research, during the investigations it appears that although migraine is a physiological disease, psychological factors have significant roles in pain management. 10 In a survey conducted in patients with chronic pain it became clear that seeking for help and accepting the pain had impacts on reduction of factors associated with the severity of the pain. Also, in a study the regression equation regarding the prediction of physical disability showed that, accepting the pain and asking for help factors predicted less physical disability 18 And again, an investigation showed that asking for help and pain acceptation, was effective in reduction of pain-related anxiety and the severity of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is the most common mental stress encountered with individuals and none of other physical symptoms, is not the same extent as pain. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Besides, emotional control methods are the main source of understanding the emotional and behavioral dependencies of stresses and negative emotional events (Gross, 2002). Previous studies confirm the effectiveness of non-pharmaceutical and cognitive-behavioral approaches in treating headaches (Brown, Newman, Noad, & Weatherby, 2012;Nicholson, Buse, Andrasik, & Lipton, 2011). According to Neff and Germer's study (2013), there is a significant relationship between self-compassion and reduced anxiety, depression, perfectionism, neuroticism, preoccupations, and thought inhibitions.…”
Section: Introductionmentioning
confidence: 99%